Dance and light : the partnership between choreography and lighting design - Dreyer, Kevin (Routledge, 2020)
"Dance and Light examines the interconnected relationship between movement and design, the fluid partnership that exists between the two disciplines, and the approaches that designers can take to enhance dance performances through lighting design. The book demystifies lighting for the dancer and helps designers understand how the dancer/choreographer thinks about their art form, providing insight into the choreographer's process and exploring how designers can make the most of their resources. The author shares anecdotes and ideas from an almost 50-year career as a lighting designer, along with practical examples and insights from colleagues, and stresses the importance of clear communication between designers, choreographers, and dancers. Attention is also given to the choreographer who wants to learn what light can do to help enhance their work on stage. Written in short, stand-alone chapters that allow readers to quickly navigate to areas of interest, Dance and Light is a valuable resource for lighting design classes wishing to add a section on dance lighting, as well as for choreography classes who want to better equip young artists for a significant collaborative partnership"--